Papric Ethanol Extract Test (Capsicum Annuum) on Blood Sugar Levels of Wistar Rat (Rattus Norvegicus) Induced Alloxan - Pratama Zendrato; Dara Ananda (Archives of The Medicine and Case Reports, 2021)
This study aims to determine the effect of paprika ethanol (capsicum annuum) on blood sugar levels of alloxan-induced Wistar rats (rattus norvegicus). This type of research is experimental. The method used was pre test and post test with control group design. The results of this study indicate that for Post Test 1 or after being given treatment for 7 days, the average result shows that there is an effect of giving red paprika ethanol extract on blood sugar levels in Wistar rats where the significant value of each treatment is all less than 0.05. For Post Test 2 or after being given treatment for 14 days, only at a dose of 250 that has no effect on blood sugar levels of the rats, because the significant value is 0.813 greater than 0.05, for other treatments it has a significant effect because the significant value is more smaller than 0.05.